Issues and Challenges Of Scientific Research In The Arab World: Obstacles And Solutions - Knaza, Mouhamed fouzi (Milev Journal of Research and Studies, 2018)
This article deals with the problematic of scientific research in the Arab world, as an attempt from a constructive – functional perspective, focusing on the constructive elements that cause deterioration in this sector, by defining the disabilities, shortcomings and the dysfunction caused by incompatibility of the different variables involved in the research work. Therefore, we will try to present a perception of a plan centered on some effective indicators contribute to the establishment of a sectoral research policy for research centers and universities as the main incubator of the researcher and his creative ideas.